Teacher readiness in terms of technological skills in facing artificial intelligence in the 21st century education era - Adzkia, Mhd Safiq; Refdinal, Refdinal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Students currently being faced are students who were born in the digital era, they are accustomed to things related to the internet, they are already good at playing the gadgets they have, while there are still teachers who are not very good at using various applications for learning. This study aims to determine the readiness of vocational high school teachers to face artificial intelligence in the era of 21st century education.The type of research used in this study is a descriptive quantitative method. The population is 274 teachers. The number of samples is 73 teachers who are drawn using the proportional random sampling technique. The data collection technique is carried out through primary data in the form of questionnaires filled out by respondents and secondary data in the form of data obtained from the school. The test results show the unpreparedness of teachers in terms of technological skills influenced by critical thinking, problem solving, communication, collaboration and creativity. The conclusion of this study is that there is a positive and significant relationship between critical thinking and problem solving, communication, collaboration and creativity on the readiness of vocational high school teachers in facing artificial intelligence in the 21st Century Education era.